2014
DOI: 10.1038/cddis.2014.222
|View full text |Cite|
|
Sign up to set email alerts
|

SPAG5 upregulation predicts poor prognosis in cervical cancer patients and alters sensitivity to taxol treatment via the mTOR signaling pathway

Abstract: Previously, we found that sperm-associated antigen 5 (SPAG5) was upregulated in pelvic lymph node metastasis–positive cervical cancer. The aim of this study is to examine the role of SPAG5 in the proliferation and tumorigenicity of cervical cancer and its clinical significance in tumor progression. In our study, SPAG5 expression in cervical cancer patients was detected using quantitative real-time polymerase chain reaction, western blotting, and immunohistochemistry; cervical cancer cell function with downregu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
74
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(82 citation statements)
references
References 28 publications
8
74
0
Order By: Relevance
“…Illumina whole‐genome gene expression microarrays show that SPAG5 expression is highly up‐regulated in non‐small‐cell lung cancer tissues . High levels of SPAG5 in cervical cancer patients predict poor disease‐free survival . In prostate cancer, SPAG5 expression is gradually increased in prostate cancer progression and the high expression of SPAG5 is correlated with clinical stage, Gleason score, lymph node metastasis, and biochemical recurrence .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Illumina whole‐genome gene expression microarrays show that SPAG5 expression is highly up‐regulated in non‐small‐cell lung cancer tissues . High levels of SPAG5 in cervical cancer patients predict poor disease‐free survival . In prostate cancer, SPAG5 expression is gradually increased in prostate cancer progression and the high expression of SPAG5 is correlated with clinical stage, Gleason score, lymph node metastasis, and biochemical recurrence .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, recent studies have reported an important role of SPAG5 in cancers. High expression of SPAG5 is frequently detected in cancer tissues and is correlated with tumour progression and poor prognosis . SPAG5 is involved in regulating the proliferation, apoptosis, migration and invasion of tumour cells .…”
Section: Introductionmentioning
confidence: 99%
“…Given that drugs such as the anthracyclines and taxane, which interfere with the normal progression of mitosis, belong to the most successful chemotherapeutic compounds that are currently used for anticancer treatment, SPAG5 could be a molecular target on which the development of "next generation anti-mitotic drugs" could be based. Recent studies in cervical cancer 34,35 reported SPAG5 to be up-regulated, and demonstrated that the downregulation of SPAG5 inhibited cell proliferation/growth, increased apoptosis and hindered cell migration and invasion. 35 Furthermore, it is possible that "anti-SPAG5…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in cervical cancer 34,35 reported SPAG5 to be up-regulated, and demonstrated that the downregulation of SPAG5 inhibited cell proliferation/growth, increased apoptosis and hindered cell migration and invasion. 35 Furthermore, it is possible that "anti-SPAG5…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation